Ritus ayoa, dalam tari aseak bebuak kerinci - Deli Monica Asmara; Erlinda Erlinda; Martion Martion (Titian: Jurnal Ilmu Humaniora, 2021)
The dance work entitled "Ritu Ayoa" is a dance work that starts from the Aseak ceremony in the Kerinci community, Jambi Province. This work is done with the format of presenting the results of imagination that provides an alternative creation in the form of dance compositions. Mainly is the form of composition whose cultivation is based on the Aseak ritual event for the treatment that exists in the Kerinci community. The form or structure of the performance of the dance work "Ritu Ayoa" consists of three parts. The first part describes or reveals the activities of the handler with his environment which emphasizes water as a vital thing in life. The second part describes the conflict that occurs in the Aseak ritual in medicine, and the final part reveals the environmental balance that focuses or describes water that must be preserved in life. These three parts become a unified form of choreography in harmony with the musical bonds that are part of strengthening the dance work.